On the Rate Structure of the American Life Insurance Market - Winter, Ralph A. (Journal of Finance, 1981)
This article re-examines the conclusion of previous studies that price dispersion is extreme in the American whole life insurance market. We take an axiomatic approach to the problem of measuring “price” dispersion in the market for the multiparameter whole life contracts, studying the distribution across contract offers of a price index which is uniquely determined by two conditions. In contrast to the accepted wisdom, we find that the derived measure of price dispersion is only 3.6% and that much of this dispersion can be accounted for by measurement error.